Pengembangan Media Pembelajaran Video Untuk Membaca Permulaan Tema 4 Keluargaku Kelas 1 SD Ar-Rahman Darul Ilmi - Ani Sri Mulyani; Yosi Aryanti; Deni Soidin; Kusmiati, Elly (Prodi PGMI STAI Sabili Bandung, 2023)
This research aims to explain the use of video media reading the beginning of topic 1, My Family, for elementary school students, in language learning content of recognizing words of praise, invitation, apology, and thanks. This research and development are carried out through the Sugiyono development process, which consists of 10 steps, namely: potential problem phase, data collection phase, product design phase, design validation phase, design review phase, product trial phase, product verification phase, user trial phase, product release phase, and mass production phase (first video reading). The subjects in this study were grade I students of SD Ar-Rahman Darul Ilmi. The assessment results of the media, material and language analysis aides reached an overall figure of 92.4% meaning that the first reading video developed falls under the criteria of